The role of the respiratory tract microbiome in respiratory health - N. G. Astafieva; D. Yu. Kobzev; I. V. Gamova; I. A. Perfilova; E. N. Udovichenko; L. V. Skuchaeva; I. E. Michailova (Лечащий Врач, 2021)
The proposed review summarizes recent advances in the study of respiratory microbiota, the relationship between the upper respiratory tract microbiome and the lung, and a discussion of the possible mechanisms of influence of the microbiome on asthma and allergies. Identifying not only pathogenic bacteria, but also commensals in the respiratory tract and gastrointestinal tract (Gut- Lung axis) is an innovative approach to finding out their role in the development of inflammation and modulation of the immune response in respiratory allergies.